Carcharhinus humani sp. nov., a new whaler shark (Carcharhiniformes:Carcharhinidae) from the western Indian Ocean - White, William T.; Weigmann, Simon (Zootaxa, 2014)
A new species of whaler shark, Carcharhinus humani sp. nov., is described based on five type specimens from the western Indian Ocean near the Socotra Islands, off Kuwait, Mozambique, and South Africa. The new species represents the fifth species of the C. dussumieri/sealei group and the third species of the C. sealei subgroup. The new species is the only species of the C. sealei subgroup known from the western Indian Ocean. Within the C. sealei subgroup, C. humani differs from C. sealei in having a sharply demarcated black apical marking on the second dorsal fin which does not extend onto body surface (vs. black marking diffuse-edged and usually extending onto upper sides of trunk), a longer horizontal prenarial length (4.1–4.7 vs. 3.4–4.2% TL), and a longer preoral length (6.8–7.6 vs. 5.7–6.5% TL); C. humani differs from C. coatesi in having a taller second dorsal fin (its height 4.0–4.5 vs. 2.9–3.6% TL), a shorter first dorsal fin (its length 13.4–14.6 vs. 14.8–17.3% TL), and more vertebrae (total centra 152–167 vs. 134–147).